Parenting patterns of Vocational High School Students: A case study at Setia Bhakti Vocational High School in Tangerang City - Wardhani, Bilqis Pramudiya; Ekawati, Dian (Empathy : Jurnal Fakultas Psikologi, 2023)
This research was motivated by problems regarding parenting, difficulties in directing children to study because they get bored easily, difficulty dividing time between work and helping children when studying and difficulty in dealing with children using gadgets. This research aims to determine the parenting patterns obtained by Setia Bhakti Vocational School students and the impact obtained from parental care. The method used is a qualitative method with a case study approach. The research subjects were students of Setia Bhakti Vocational School, Tangerang City, class XI majoring in accounting who were taking online learning. Based on the data obtained, the pandemic has changed the parenting style provided by parents, where parents are not only involved in helping their children learn at home but also have to provide learning support facilities. Apart from that, working parents also have to divide their time between work and their children's needs during the online learning process. Not only that, parents must also monitor their child's development so that it does not decline and make the learning atmosphere enjoyable.